Storylistening: How narrative evidence can improve public reasoning about climate change. (2nd November 2022) - Dillon, Sarah; Craig, Claire
Abstract: Stories have cognitive value—listened to carefully and expertly, they provide knowledge. That knowledge is captured and presented in narrative evidence—the product of the expert act of critical engagement with stories, and with others' engagement with stories. Storylistening is the theory and practice of gathering narrative evidence to inform decision‐making, especially in relation to public reasoning, as part of a pluralistic evidence base. Storylistening is necessary to counter the political deployment of partial, selective, or misinterpreted narrative evidence. There are four ways in which stories can contribute to public reasoning about climate change. Stories play a role in reframing the "idea" of climate change, as well as being integral to many of the new disciplines, perspectives and knowledges drawn in as relevant by that reframing. Stories create and cohere collective identities and climate change beliefs and behavior. Narrative models complement and supplement computational models, creating an ensemble of models that more adequately covers the gaps that result from only deploying big, global, generalized models. Stories play a crucial role in enabling better anticipation for decision‐making, and storylistening can enable the use of narrative evidence from narrative futures methods, as well as perhaps improve the ways scientific evidence about the future is also listened to. Incorporating storylistening into public reasoning about climate change requires the evolution of advisory systems and of the academic humanities, and can play a role in the urgent need to democratize public reasoning about climate change. This article is categorized under: Trans‐disciplinary Perspectives > Humanities and the Creative Arts Abstract : Public reasoning about climate change would benefit from the inclusion of narrative evidence derived from storylistening, and advisory systems need to evolve to include it.